Animated Video-Based Learning Media Assisted with Powtoon on Living Things Characteristics Topic - Komang Ayu Lestari; Kadek Suranata; Gede Wira Bayu (Universitas Pendidikan Ganesha, 2022)
The lack of learning media development and learning that is still based on books causes learning activities to seem less innovative. It has an impact on low student learning outcomes. This research aims to develop an animated video with the help of the Powtoon application in natural science subjects on the topic of living things. This type of research is designed using the 4-D development model. The research subjects were learning media experts, material experts, media experts, practitioners' responses, and student responses. Data collection methods used in this study are observation, questionnaires, rating scales, and documentation. The instrument used to collect data is a questionnaire. Data analysis techniques used in development research are qualitative descriptive statistical analysis techniques and quantitative descriptive statistical analysis techniques. The research results are the results of the validity of media experts at 94.5% (very good). The results of learning material experts get a score of 93.8% (very good). The teacher's practicality test results were 97.7% in the very practical predicate and did not need to be revised. Students' results of the practicality test obtained a percentage of 95% (very practical). It was concluded that this Powtoon animation video media is feasible to use in the learning process. Powtoon animated video media makes learning easy for students and motivates them to learn.